2015
DOI: 10.1007/s12288-015-0604-4
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Related Acute Lung Injury (TRALI): A Single Institution Experience of 15 Years

Abstract: Transfusion related acute Lung injury (TRALI) though a serious blood transfusion reaction with a fatality rate of 5-25 % presents with acute respiratory distress with hypoxaemia and noncardiac pulmonary oedema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In total, 48 studies reported rates for five types of transfusion reactions, providing a total of 120 separately reported transfusion reaction rates—allergic transfusion reactions (35), FNHTRs (18), transfusion‐associated circulatory overload (TACO) (9), anaphylactic transfusion reactions (12), and transfusion‐related acute lung injury (TRALI) (46). The 48 studies, many of which reported on transfusion reaction rates for multiple plasma types, investigated AI‐FFP (4), SDP (8), MO‐FFP (7), MB‐FFP (3), and MS‐FFP (39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 48 studies reported rates for five types of transfusion reactions, providing a total of 120 separately reported transfusion reaction rates—allergic transfusion reactions (35), FNHTRs (18), transfusion‐associated circulatory overload (TACO) (9), anaphylactic transfusion reactions (12), and transfusion‐related acute lung injury (TRALI) (46). The 48 studies, many of which reported on transfusion reaction rates for multiple plasma types, investigated AI‐FFP (4), SDP (8), MO‐FFP (7), MB‐FFP (3), and MS‐FFP (39).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were performed between 2001 and 2016 in 20 different countries and included observations from over 25 million transfusions. Complete study characteristics and extracted data, along with their ROBINS‐I evaluations, are provided in Table S1 (available as supporting information in the online version of this paper) …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] The frequency of this disease is about 1:5000 patients receiving blood or components, being the fourth most common adverse transfusion reaction and the third leading cause of death associated with transfusion. 4,5 TRAVI has a high mortality rate both in adult and pediatric population (63.7%). 1 The etiology possibly can be caused in the 65-85% of all reported TRALI cases by anti-HLA (human leukocyte antigen) antibodies class I, II, which can be present in the serum of the recipient or donor and react with the donor's or recipient's leukocytes, respectively and by non-immune-mediated TRALI can be attributed to transfusion of biologically active compounds, which are accumulated in stored blood components such as bioactive lipids, proinflammatory cytokines or platelet microparticles with high procoagulant activity.…”
Section: Introductionmentioning
confidence: 99%
“…8 The antecedents of patients with TRAVI include patients with hematologic malignancy undergoing induction chemotherapy major surgery, alcohol dependence, kidney failure, and severe liver disease massive transfusion (replacement of total volume for 4days) and cytokine administration (Granulocyte Colony Stimulating Factor (GCSF), it's important to know that many clinical studies have shown that patients with more severe underlying disease are at higher risk of developing lung injury after transfusion. 4,8,9 The clinical presentation is characterized by dyspnea, hypoxemia, arterial hypotension, non-cardiogenic, acute pulmonary edema and fever. 5 During the physical examination the patient showed diffused pulmonary crackles and decreased breath sounds in complementary studies such as chest radiography the patient shows faint, diffuse alveolar infiltrates consistent with pulmonary edema, it's important not to be confused with other conditions including transfusion-associated circulatory overload (TACO), pneumonia, and acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%
“…There are many reports on the occurrence of TRALI after IVIg administration [24][25][26][27][28][29]. Anti-HLA-II IgG observed in patients after plasma transfusion is implicated in TRALI [26].…”
Section: Introductionmentioning
confidence: 99%